Morphological variability of 65 amaranth accessions from the Cajamarca Region, Peru - Escalante Ortiz, Lucia Emperatriz (2023)
Amaranth is a promising crop for the Cajamarca region and Peru. The National Institute of Agrarian Innovation (INIA) from Peru preserves a national collection of 552 amaranth accessions; however, there needs to be a detailed study of the morphology of these materials. In this research, 65 accessions were morphologically characterized based on their place of origin, using 21 descriptors standardized by INIA-Peru. The clustering of accessions and principal component analysis showed the presence of 38 groups and a duplication rate of 41.5% of accessions at a taxonomic distance of 0.62. In addition, 18 morphological characters that significantly contributed to morphological variability were identified and explained by the first six principal components. Due to the scarcity of studies on amaranth, it is recommended to conduct more characterization and molecular studies to obtain better approximations of the genetic diversity of the amaranth germplasm to be used on amaranth plant breeding programs.